(untitled) (Palíndromo, 2022)
This research reflects on Plantation as a paradigmatic and conceptual figure to think about the reduction of the ontological plurality of artistic expressions in modernity. Implanted during the European colonial regime, the figure of the Plantation in the new world changed the ways of thinking, seeing, cultivating and weaving relationships, for this reason, a series of researchers in the human sciences named this new regime Plantationocene. Starting from these investigations and using the creation of the category “African art” in this period, it will be investigated how Plantation conceptually modifies the relations of artistic making. As a counterpoint and possibility of resistance, localized and endogenous perspectives on artistic and aesthetic productions are defended, in which the aesthetics of aché and its imbrications with Yoruba arts and world production are presented as an example and possibility.